A Comparative DFT Study of Bandgap Engineering and Tuning of Structural, Electronic, and Optical Properties of 2D WS2, PtS2, and MoS2 between WSe2, PtSe2, and MoSe2 Materials for Photocatalytic and Solar Cell Applications - Jameel, Muhammad Hasnain; Roslan, Muhammad Suf; Mayzan, Mohd Zul Hilmi; A. Shaaban, Ibrahim; Haider Rizv, Syed Zuhaib; Agam, Mohd Arif; Saleem, Shahroz; A. Assiri, Mohammed (2023)
In early twenty-frst century, 2D materials are among the most systematically reachable in the feld of material science. Due to its semiconductor properties, the transition metal dichalcogenide family has received attention. In the current research, the GGA-PBE simulation approximation is used to tune energy bandgap (Eg), optical and electronic properties of TMDCs (transition metal dichalcogenide) such as WS2, PtS2, MoS2, WSe2, PtSe2, and MoSe2 by density functional quantum computing simulation. It is calculated that the energy bandgap (Eg) of WSe2, PtSe2, and MoSe2 shows a decrement trend with small Eg 1.43, 0.88, and 0.74 eV respectively as compared to WS2, PtS2, and MoS2 with large Eg 1.96, 1.62, and 1.50 eV respectively with direct to indirect semiconductor nature. In WSe2, PtSe2, and MoSe2 materials the extra gamma active states created which help to build the conduction and valance bands as a consequence of decrement in the Eg. A detailed study of optical conductivity shows that optical conductance increases with bandgap decrement (1.96–0.74 eV) in ultraviolet pattern with small shifts at larger energy bands. 2D-TMDCs MoS2 and MoSe2 shows maximum optical conductivity and absorbance 105× 103 Ω−1 cm−1, 2.78× 105 cm−1 and 85× 103 Ω−1 cm−1, 3.1× 105 cm−1 respectively as compared to WS2, PtS2, WSe2 and PtSe2 due to small energy bandgap. In the refectivity, a signifcant increment is found in MoS2 and MoSe2 semiconductor materials as compared to WS2, PtS2, WSe2, and PtSe2 due to the decrement in the bandgap. The family of TMDCs such as WS2, PtS2, MoS2, WSe2, PtSe2, and MoSe2 are a capable semiconductors materials has a enhanced surface area for absorbance of photo-generated charge carriers and decrease the photo-generated charge carriers recombination rate and increment the charge transportation. The optical properties signifcantly enlarged MoS2 and MoSe2 materials have profcient energy absorbance, and refractive index as compared to WS2, PtS2, WSe2, and PtSe2 semiconductors, and all these materials are appropriate for photocatalytic and solar cell applications.